CFD analysis of directional airflow and internal baffles for improving thermal uniformity in a 4 × 6 li-ion battery module - Pham, Minhhieu; Chan, Tzi-Chi; Chu, Duc Hung; Ngo, Huu Tinh; Do, Van Tuan; Dinh, Ngoc Anh; Pham, Hong An; Nguyen, Duc Trong (Frontiers in Mechanical Engineering, 2026)
Effective thermal management for lithium-ion batteries is a key factor in preventing overheating, maintaining even heat distribution, and extending battery life. Air cooling systems are considered a simple, low-cost, and easy-to-implement solution. However, poor heat transfer efficiency and uneven airflow remain major challenges. This study investigates the impact of airflow direction and internal partitions on the thermal performance of a 4 × 6-cell lithium-ion battery module using Computational Fluid Dynamics (CFD) simulations with ANSYS Fluent software. Five cooling configurations were investigated. The results showed that the novel combination of counter-flow air with internal partitions provided the most optimal cooling performance. This synergy significantly enhanced thermal uniformity and helped maintain safer operating temperatures. Specifically, the maximum temperature Tmax decreased from 346.852 K to 314.768 K, and the temperature difference between cells ΔTmax decreased sharply from 39.7 K to only 2.9 K. The partition enhanced convection and effectively prevented airflow from short-circuiting. Nevertheless, this design also increased pressure loss and fan power consumption by approximately 10%-12% compared to the base configuration. Simulation results demonstrated the superior effectiveness of the combined counterflow and baffle design in air cooling solutions, while providing a technical basis for optimizing a low-cost, high-efficiency, and easily deployable Battery Thermal Management System (BTMS) in practice.